The Effect Of The EDGA Model On The Achievement Of Arabic Language Among Fourth Grade Literary Students (Journal of the College of Basic Education, 2024)
The research aims to identify the impact of the model (EDJA) on the achievement of Arabic language among fourth-grade literary students. The researcher followed the experimental approach and chose to design the two groups (experimental and control) with a post-test from the research community consisting of secondary schools and preparatory government days of the General Directorate of Education in Baghdad Governorate/Karkh II. The sample was selected by a simple random method consisting of 60 students at Basra High School for Girls and was randomly divided into two groups (the control group and the experimental group. Each group consisted of 30 students. A proficiency test was conducted for each of the students' chronological age, calculated in months, the academic achievement of the parents, the grades of the Arabic language subject in the ministerial exam for the third intermediate grade for the previous academic year (2022-2023), language ability, and intelligence. Then the researcher tried to control a number of extraneous variables that the literature and previous studies indicated might affect this type of experimental design. The researcher prepared a test to measure achievement consisting of 38 items, 34 items of objectivity tests, a multiple-choice type, four alternatives, one of which is correct, and four paragraphs of the article type, applied to the experimental and control research groups at the end of the experiment. Using the t-test of two independent samples, the research yielded. There is a statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students and the average scores of the control group, in favor of the experimental group.